2016
DOI: 10.1016/j.jtcvs.2015.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Caprini venous thromboembolism risk assessment permits selection for postdischarge prophylactic anticoagulation in patients with resectable lung cancer

Abstract: One third of VTE events occurred after discharge. Postoperative VTE incidence was correlated with increasing Caprini scores. Patients in the high risk group had an incidence of 10.3%. Elevated scores may warrant extended chemoprophylaxis for patients after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 30 publications
2
98
0
Order By: Relevance
“…To date, risk assessment tools, including the Caprini VTE risk model, have demonstrated success in identifying patients at risk for postdischarge VTE [28,29]. Our data corroborate several risk factors used in the Caprini model, including older age, obesity, and extended operative duration [29].…”
Section: Commentsupporting
confidence: 75%
“…To date, risk assessment tools, including the Caprini VTE risk model, have demonstrated success in identifying patients at risk for postdischarge VTE [28,29]. Our data corroborate several risk factors used in the Caprini model, including older age, obesity, and extended operative duration [29].…”
Section: Commentsupporting
confidence: 75%
“…The Hachey and colleagues cohort study 20 was a retrospective chart review from 2005 to 2013, and as such, all reported cases were diagnosed secondary to symptoms, potentially explaining the overall lower VTE incidence. Additionally, Hachey and colleagues 20 reported that 92% of VTE occurred in postthoracotomy patients, whereas our cohort consisted of 47% incident cases following video-assisted thoracoscopic surgery, and so the results of Hachey and colleagues 20 may not be comparable to institutions with a much greater proportion of minimally invasive cases.…”
Section: Discussionmentioning
confidence: 76%
“…Despite analysing data from over 10,660 patients, all but one of the included studies were retrospective with marked heterogeneity, limiting the ability to pool the data. The VTE estimates reported in these reviews are in stark contrast to more recent literature demonstrating a higher incidence rate (7,17,18). Using computed tomography (CT) pulmonary angiogram and lower extremity venous Doppler ultrasound screening, we recently found that the prevalence of post-lung cancer resection VTE was 12.1%, and that over 75% patients were asymptomatic (6), highlighting the potential underdetection of this phenomenon.…”
Section: Discussionmentioning
confidence: 91%